KATA-KATA PINJAMAN DALAM ISTILAH SEPAKBOLA (SEBUAH KAJIAN MORFOLOGI) - Ginanjar, Riki (Program Studi Sastra Inggris, Fakultas Sastra, Universitas Komputer Indonesia Bandung, 2018)
Different language has its own difference in writing or pronunciation Sometimes, an activity may have not the actual word to express it. When one language has no word to express, the word from otherâ€™s language is used. The word itself is known as loanword. This case mostly appears in the football area. This article entitled â€˜Loan Words in Football Terminologyâ€™ explains about the loan word which is usually used in the football terminology. The writer used the dictionary about football terminology â€œKamus Istilah Sepakbolaâ€ by Nugraha Edy in order to find the data to be analyzed. The writer also uses the theory of Haugen â€œThe ecology of Languageâ€ which will describe how the loan word formed. Before analyzing the data, the writer looked for the terminology in the data source and then analyzes it using the theory stated. At the end of analysis, the writer finds that many of football terminology in English has not be converted to Indonesian, so Indonesian has to loan English terminology to express it.